A field test of empathetic refutational and motivational interviewing to address vaccine hesitancy among patients - Angelo Fasce; Mirela Mustață; Alexandra Deliu; Dawn Holford; Linda Karlsson; Virginia Gould; Gheorghe Gindrovel Dumitra; Dana Farcasanu; Iulia Vișinescu; Pierre Verger; Stephan Lewandowsky (npj Vaccines)
Abstract Vaccine hesitancy is among the most concerning public health issues due to declining immunization rates worldwide. We report a mixed-methods field test of two conversational techniques that allow for an empathetic dialogue on vaccination between health care professionals and patients: Empathetic-refutational interviewing (ERI) and motivational interviewing (MI). Thirty Romanian general practitioners were assigned to an untrained control group and to two experimental groups in which they were trained in ERI or MI. After training, physicians had conversations on HPV and influenza vaccines with 334 patients who were hesitant to receive a vaccination. Patients of physicians in the ERI group demonstrated larger increases in positive attitudes toward vaccines and willingness to get vaccinated, while a greater proportion of patients in the MI group scheduled vaccination appointments. Interviews with participating physicians revealed overall satisfaction with the conversational techniques. Empathetic interpersonal communication can have a substantial positive impact on vaccination rates, especially for vaccines subject to mass misinformation campaigns.